2018
DOI: 10.1038/s41598-018-24862-6
|View full text |Cite
|
Sign up to set email alerts
|

Human limbal niche cells are a powerful regenerative source for the prevention of limbal stem cell deficiency in a rabbit model

Abstract: In this article, human limbal niche cells (LNC) or bone marrow derived mesenchymal stem cells (BMMSC) were used to prevent limbal stem cell deficiency (LSCD) in an alkali burn rabbit model and their results were compared. The epithelial cell defect area, corneal neovascularization, and the print cell cytometry were quantified to grade the severity of LSCD. Three months after the alkali burn, a partial LSCD was observed in the control group (no treatment) indicated by chronic corneal epithelial defects, positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
(61 reference statements)
2
38
0
Order By: Relevance
“…In this study, Genechip was used to compare gene expression profiles between human LNCs and BMMSCs and RT-qPCR was used to verify the Genechip results. Both Genechip and RT-qPCR results showed that the expression of CD73, CD90, CD105, PDGFRβ, Vimentin, SCF and KIT in LNC were higher than that from BMMSC, consistent with our previous reports [2,17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, Genechip was used to compare gene expression profiles between human LNCs and BMMSCs and RT-qPCR was used to verify the Genechip results. Both Genechip and RT-qPCR results showed that the expression of CD73, CD90, CD105, PDGFRβ, Vimentin, SCF and KIT in LNC were higher than that from BMMSC, consistent with our previous reports [2,17].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, we have shown LNC can maintain the stemness of LEPCs better than BMMSC when co-cultured in 3D Matrigel, both of which could form spheres after ten days of culture, although LEPC co-cultured with LNC expressed higher level of p63α but lower level of CK12 [1,2]. Animal experiments verified these observations wherein both subconjunctivally injected LNCs and BMMSCs prevented LSCD caused by alkali burn, yet LNC treated corneas had less corneal opacity and faster epithelial healing [17]. Although these results suggest LNC are therapeutically more advantageous than BMMSC for LSCD, the mechanism remains unclear.…”
Section: Ivyspringmentioning
confidence: 54%
See 1 more Smart Citation
“…that they play important roles in regulating LESCs survival and development. 22,38,[41][42][43][44][45][46] In addition, as shown above, LNCs act in a paracrine fashion to support LESCs in vitro, and so, we decided to analyse whether SOX10 acts through growth factors to influence the survival of LESCs in LNCs. To identify which factors might be involved, we compared the expression of a series of growth factor genes in si-Sox10 transfected LNCs vs si-C or mock-transfected LNCs.…”
Section: Sox10 Controls the Ability Of Lncs To Serve As A Niche Formentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Previous results have shown that LNCs support self-renewal of LESCs, 21 and LNCs transplants prevent LSCD in an alkali burn rabbit model. 22 They likely do this by secreting paracrine factors including KITL, 22 but the detailed mechanisms of KITL regulation in LNCs and how KIT, KITL and its downstream signal pathways are involved are not clearly understood. Here, we use both in vivo and in vitro approaches to provide insights into the regulation of KITL in LNCs and its action in LESCs.…”
mentioning
confidence: 99%